CLASSROOM INTERACTION IN THE TEACHING OF SPEAKING FOR THE EIGHTH GRADERS AT MTs SURYA BUANA MALANG - RISMA KARTIKA DEWI; WINARTI - (Fakultas Sastra Universitas Gresik, 2017)
The goal of teaching including teaching speaking should improve students' communicative skills. To achieve the goal, students in their learning speaking should be provided a lot of opportunities to communicate using the target language with both their teacher and other students. Therefore, the activities which occur in the classroom that intend to improve speaking abilities should be presented in interaction. In order to make the classroom interactions more effective, the importance of teacher talk is vital since the organization of the classroom and the process of acquisition are achieved through the teacher talk. This study finds that there are some categories of teacher talk and student talk in the teaching of speaking.